Evaluation of the Knowledge of Women of Childbearing Age with Epilepsy about the Impact of Their Disease in Contraception, Pregnancy and Breastfeeding: A Multicenter Cross-Sectional Study - Lopes das Neves, Pedro (2023)
Introduction: The interaction of antiseizure medication with contraceptives, its potential teratogenicity and implications in pregnancy and breastfeeding are aspects to consider in the neurological care of women with epilepsy of childbearing age. To ensure the commitment in therapeutic decisions and the appropriate planning of maternity, it is essential that women are informed about the implications of their disease in these domains. The main aim of this study was to assess the knowledge of women of childbearing age with epilepsy concerning the impact of epilepsy in contraception, pregnancy and breastfeeding. As secondary aims we defined (1) the demographic, clinical and therapeutic characterization of this group of patients, (2) the identification of variables that correlated with the level of knowledge of women with epilepsy, and (3) the identification of preferential methods to acquire new knowledge about epilepsy.Material and Methods: The study was observational, cross-sectional and multicentric, and was carried out in five hospitals of the Lisbon metropolitan area. After identifying all women of childbearing age with epilepsy followed in the epilepsy clinic of each center, we applied an electronic questionnaire based on a non-systematic review of the literature.Results: One hundred and fourteen participants were validated, with a median age of 33 years. Half of the participants were on monotherapy, and the majority had no seizures in the last six months. We identified important gaps in the participants’ knowledge. Sections about complications and administration of antiseizure medication during pregnancy were the ones with the worst results. None of the clinical and demographic variables correlated with the final questionnaire score. Having had a previous pregnancy and the desire to breastfeed in a future pregnancy were positively correlated with the performance in breastfeeding section. Face-to-face discussion during medical outpatient visits was selected as the preferential method to learn about epilepsy, and the internet and social media were the least preferred ones.Conclusion: The knowledge of women of childbearing age with epilepsy in the Lisbon metropolitan area concerning the impact of epilepsy in contraception, pregnancy and breastfeeding seems to have significant gaps. Medical teams should consider engaging in patient education particularly during outpatient clinics.